Pemberdayaan Masyarakat Melalui Pengembangan Keterampilan, Penguatan Kelembagaan, dan Peningkatan Partisipasi dalam Mempersiapkan Desa Wisata - Rianto, Rianto; Octarina, Dian; Nurmalinda, Elda; Riyadi, Agus (LPPPM STAI Darul Hikmah Bangkalan, 2024)
The purpose of this activity is to contribute positively to enhancing the capacity of the local community, both in knowledge and skills, so that they can manage agricultural potential as educational tourism attractions that benefit their economic and social well-being. The implementation methodology includes steps and strategies such as field research and in-depth interviews to identify local potential. Once the potential is identified, technical guidance is provided gradually and continuously to improve the community's capacity to manage agricultural potential into educational tourism attractions. These steps include training on processing agricultural products, marketing strategies, and developing sustainable tourism attractions. The results of the activity show an increase in the community's knowledge and skills in processing agricultural products such as tobacco, chilies, and melons into value-added products, such as souvenirs for visitors. The results and discussion of this activity also highlight the significant positive impact on the community's perspective regarding tourism potential, while also providing an analysis of the impact seen through the village's economic growth. This activity succeeded in changing the community's perspective on tourism potential and positively contributed to the development of the village as a tourism destination.